Pengaruh Penerapan Green Accounting, Kinerja Lingkungan, dan Corporate Social Responsibility Terhadap Nilai Perusahaan - Laras Bela Utami; Iwin Arnova; Helmi Herawati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of green accounting implementation, environmental performance, and corporate social responsibility (CSR) on company value. The focus of this study is on manufacturing companies in the basic industry and chemical sector, chemical sub-sector, listed on the Indonesia Stock Exchange (IDX) during the period 2019–2024. The main question to be answered in this study is to what extent the implementation of green accounting, environmental performance, and CSR can affect company value, and whether the three variables simultaneously contribute significantly to increasing company value. The research method used is a quantitative approach with multiple linear regression analysis techniques. Secondary data is obtained through annual reports published by the related companies. The sample selection was conducted using purposive sampling method based on certain criteria, such as the availability of data related to green accounting, environmental performance, and CSR during the research period. The results of the study indicate that partially, the implementation of green accounting and environmental performance do not have a significant effect on company value, while CSR shows a significant effect on company value. Simultaneously, the three independent variables have a significant effect on company value.